Comparison Of Bankruptcy Risk Of Sharia General Bank In Asia - Putri Acebeli; Umiyati Umiyati (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
This study is aims to compare the risk of bankruptcy in the Islamic Comercial Bank in Asia. The sample used in this study is five Islamic Commercial Bank in five countries in the Asian continent in 2014-2018. The method used in measuring bankruptcy rates is the Altman z score bankruptcy analysis. Tests conducted in this study are the normality test and the different test with the Kruskal-Wallis tests followed by the Mann Whitney Post Hoc Test. This study indicates this study indicate that the average z score that measures the level of the bankruptcy of Islamic Commercial Bank in Asia is worth 6.6 points. This value shows that Islamic banks in Asia are included in a healthy companies and far from the risk of bankruptcy. Based on Kruskal Wallis Nonparametric Test indicates that there are significant differences from the level of the bankruptcy of Islamic Commercial Bank in Asia with a value of ρ value 0.00 <Significance Value (α = 0.05).